2018
DOI: 10.4274/mirt.10438
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking of a Simple Scintigraphic Test for Gastro-oesophageal Reflux Disease That Assesses Oesophageal Disease and Its Pulmonary Complications

Abstract: Objectives:Gastro-oesophageal reflux disease (GORD) is both common and troubling with a prevalence of 20-40%. We assessed the utility of a scintigraphic reflux study to evaluate the oesophageal and extra-oesophageal manifestation of disease compared to the standard tests such as pH monitoring and manometry.Methods:Patients were recruited into a prospective database of referrals to a tertiary referral center for either resistance to maximal medical therapy or extra-oesophageal symptoms of GORD. Data included 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Recently, Burton et al have suggested the use of scintigraphy with Tc-99m to identify alterations in the esophageal motility and lung aspiration of refluxate [4].…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Burton et al have suggested the use of scintigraphy with Tc-99m to identify alterations in the esophageal motility and lung aspiration of refluxate [4].…”
Section: Diagnosismentioning
confidence: 99%
“…The 2006 Montreal consensus defined GERD as a condition that develops when the reflux of the stomach contents causes troublesome symptoms and/or complications into the esophagus [1]. Tissue damage related to GERD range from esophagitis to Barrett's esophagus and esophageal adenocarcinoma; troublesome symptoms attributable to reflux can be esophageal (heartburn, regurgitation) or extra-esophageal (EE) [2][3][4][5]. GERD can be further classified by the presence of erosions on endoscopic examination (Erosive Reflux Disease [ERD] and Nonerosive Reflux Disease [NERD]) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Reflux scintigraphy performed with the correct protocol has been shown by our group to more accurately detect upper airway reflux and lung aspiration with good response to anti-reflux surgery in selected patients [36,37]. In LPR patients with symptoms refractory to high dose PPI therapy undergoing combined oesophageal and scintigraphy studies, a high incidence of non-acid reflux is the rule often with reduced lower oesophageal sphincter tone.…”
Section: Diagnosismentioning
confidence: 95%
“…The technique implemented at Site A has been validated against the standardized current diagnostic tests for GORD (Burton et al, 2018(Burton et al, , 2020Falk et al, 2015). Findings in 25 normal volunteers have demonstrated that 32% have asymptomatic upright reflux which does not reach the pharynx/laryngopharynx.…”
Section: F I G U R Ementioning
confidence: 99%
“…The technique at Site A has been validated against the current standards for testing of GORD and shown good correlation with pH/impedance and manometry (Burton et al, 2018(Burton et al, , 2020Falk et al, 2015) and for the first time, allowed the direct visualization of refluxate at extraoesophageal sites with SPECT/CT imaging.…”
mentioning
confidence: 99%